PROBLEMATIKA PENDIDIKAN DALAM PERSPEKTIF SOSIAL HUMANIORA MENGUAK GRADASI KEMANUSIAAN - I Putu Suardipa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Social problems in every society have a significant level of cultural diversity andinteractionism patterns with one another that are very different. This deflation involves the levelof cultural development and the condition of its natural environment. These problems can bemanifested in moral issues, political problems, religious problems and other problems. Humanitieseducation is an educational material that reflects human integrity and helps people to becomemore humane, which is to help humans to actualize existing potentials, so that eventually acomplete human being is formed, which has emotional maturity, moral maturity and spiritualmaturity. Various kinds of cases of violence that occur in social life, anarchist actions andviolations of human values have even become everyday. The indicator is that education has notplayed a significant role in the process of building a national personality with a social andhumanitarian spirit. Apparently, humans must be more “humanized” again. The protractednation’s decline is also related to educational failures in the past which resulted in adehumanization process. The educational process that emphasizes the development of personalityincludes a broader process, namely improving thought processes, feeling, and acting. With thehope of students being able to practice the values of life which include the values of truth(verum), beauty (pulcrum) and kindness (bonum).Keywords: Educational Problems, Social Humanities